FOREIGN CULTURAL POLICY IN THE INTERBELLUM - Kessel, Tamara van. Link ([S.l.])
1 online resource
Keywords: This book considers the growing awareness in the wake of World War I that culture could play an effective political role in international relations. Tamara van Kessel shows how the British created the British Council in support of those cultural aims, which took on particular urgency in light of the rise of fascist dictatorships in Europe. Van Kessel focuses in particular on the activities of the British Council and the Italian Dante Alighieri Society in the Mediterranean area, where their respective country's strategic and ideological interests most evidently clashed.